GEOGRAPHY STUDENTS PERCEPTION OF ONLINE LEARNING SYSTEMS IN COVID PANDEMIC CONDITIONS 19 - Rosalina Kumalawati; Karnanto Hendra Murliawan; Astinana Yuliarti (Journal Learning Geography, 2020)
Indonesia is one of the developing countries affected by Covid-19 . The development of Covid-19 has increased in recent months . This research is quantitative descriptive. The population in the study were 88 students of the Geographic Study Program at Lambung Mangkurat University . The population is equal to the number of samples. D ata primary and secondary data used in this study . Data processing by way of classifying the results of the questionnaire, and calculate the percentage. Data was collected by survey method and analyzed using Rank Spearman's non-parametric statistical method. The findings of the study were to determine the Geography Student's Perception of the Online Learning System so that it could be used to overcome learning problems in the Covid-19 pandemic conditions. Limitations of the study is to limit the perception of geography student at an online learning system for the subject of Hydrology , and Meteorology . Perceptions of subjects are limited to two subjects . The results showed the Geography Student's Perception of Online Learning System in Covid-19 Pandemic Conditions for Hydrological subjects was low while the Meteorology Climatology course was moderate. Students' skills in using the internet in Geography students for the Climatology and Hydrology and Meteorology courses are at a moderate level. The implementation of the online learning system must be supported by all students and all parties. The online learning system is expected to be one of the solutions in learning in the Covid-19 pandemic conditions, so as to reduce the spread of Covid-19. Indonesia merupakan salah satu negara berkembang yang terkena Covid-19. Perkembangan Covid-19 meningkat dalam beberapa bulan terakhir. Penelitian ini adalah deskriptif kuantitatif. Populasi dalam penelitian adalah mahasiswa Program Studi Geografi FISIP Universitas Lambung Mangkurat sebanyak 88 orang. Jumlah populasi sama dengan jumlah sampel. Data primer dan data sekunder digunakan dalam penelitian ini. Pengolahan data dengan cara mengelompokkan hasil kuesioner, dan menghitung persentase. Data dikumpulkan dengan metode survai dan di analisis menggunakan metode statistic non-parametrik Rank Spearman. Temuan dari penelitian adalah mengetahui Persepsi Mahasiswa Geografi terhadap Sistem Pembelajaran Online sehingga dapat digunakan untuk mengatasi masalah pembelajaran pada kondisi pandemic Covid-19. Keterbatasan penelitian adalah membatasi persepsi mahasiswa geografi pada sistem pembelajaran online untuk matakuliah Hidrologi, dan Meteorologi Klimatologi. Persepsi terhadap matakuliah dibatasi pada dua matakuliah. Hasil penelitian menunjukkan Persepsi Mahasiswa Geografi terhadap Sistem Pembelajaran Online pada Kondisi Pandemik Covid-19 untuk matakuliah Hidrologi adalah rendah sedangkan matakuliah Meteorologi Klimatologi adalah sedang. Ketrampilan mahasiswa menggunakan internet pada mahasiswa Geografi untuk matakuliah Hidrologi dan Meteorologi Klimatologi berada ditingkat sedang. Pelaksanaan sistem pembelajaran online harus didukung oleh semua mahasiswa dan semua pihak. Sistem pembelajaran online diharapkan mampu menjadi salah satu solusi dalam pembelajaran pada kondisi pandemik Covid-19, sehingga dapat mengurangi penyebaran Covid-19.